(3GdhLg GdLejd aj Yde GdNdjds - (3TYHGf Hf eMeO Hf OGhO GdehUdj, GdeYQha HGdBKGQj,J (B828 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg CMeOg TcQkG Ydi fhGdg s
(3BNQgG (B:s
(3EVeGQge hGdhba ai GdSQjY cQLR UMjM Ch ebWhY s
(3CQLhRIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B300s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B702s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais